Seroprevalence of leptospirosis among hospitalized febrile patients in Unguja Island - Ally, Ally Abdullah; Lupindu, Athumani Msalale; Machang’u, Robert; Katakweba, Abdul Selemani (Journal of Ideas in Health, 2023)
Background: Leptospirosis is one of the neglected causes of febrile illness and death in developing countries, including Tanzania. The study aims to determine the seroprevalence of leptospirosis among hospitalized febrile patients in Unguja Island. Methods: A cross-sectional study was carried out in the three selected hospitals in Unguja Island between January and March 2022. A total of 402 participants with febrile illness were enrolled in the study, and blood samples were collected for sera preparation. Microscopic agglutination test (MAT) was used to detect antibodies against five Leptospira serovars, including Sokoine, Lora, Pomona, Grippotyphosa, and Hebdomadis. All sera samples reacted with MAT titers≥1:160 were counted as positive, MAT titers ranging from 1:20 to 1:80 were counted as exposed to Leptospira bacteria while the absence of agglutination was regarded as negative. The data was analyzed using SPSS version 26, 2019. Descriptive and logistic regression was performed, and p≤0.05 was considered statistically significant. Results: The mean age of study participants was 29.62 ±16.34, with a range of 0 days to 80 years. Most of them were females (64.2%) and unemployed (67.9%). The overall seroprevalence of leptospirosis was 7.7% (95% CI: 5.3-10.8). Females were 1.016 times higher likelihood to have leptospirosis (AOR = 1.016, 95% CI: 0.47-2.185, p = 0.968). Participants aged 18-35 were 2.093 times more likely to be infected with leptospirosis (AOR= 2.093, 95% CI: 0.835-5.250, p = 0.115). Participants who were unemployed (AOR = 1.169, 95% CI: 0.522-2.615, p = 0.704) revealed a significantly higher likelihood of being infected with leptospirosis. The predominant Leptospira serovars circulating among febrile patients were Sokoine 44 (10.9%), Lora 25 (6.2%), Grippotyphosa 20 (5.0%), Pomona 10 (2.5%), and Hebdomadis 9 (2.2%). Conclusion: Leptospirosis is a public health threat among febrile patients in Unguja Island; therefore, it’s important to be considered in the differential diagnosis of non-malaria febrile patients for early prevention and control strategies.